Metode Microteaching dalam Mengembangkan Keterampilan Dasar Mengajar dan Efikasi Diri Mahasiswa - Muhammad Saefullah; Arini Haqiqota Hayati; Shofa Taufiqika; Mamluatul Muarifah; Arini Aula Aimatun Nisa; Eqtada Binnabil Mustofa; Misbahul Baihaqi; Ali Mustofa; Balya Jayanda Daniel; Annisa Audila Rahmawati; Khoirul Mukti; Alya Mufti Tanfirotun Khusna (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Microteaching is an innovative educator training method aimed at developing basic teaching skills and fostering student self-efficacy through a micro-scale approach. This study describes how teaching simulations with limited duration, audience size, and material focus can facilitate the transformation of pre-service teachers' pedagogical competence. Using a qualitative approach, the research found that microteaching functions as a